1964
DOI: 10.1063/1.1713516
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of an Iron—Nickel Single Crystal Ordered by Neutron Bombardment

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
106
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(116 citation statements)
references
References 1 publication
2
106
1
2
Order By: Relevance
“…Irradiation was carried out below the L1 0 to fcc order-disorder transformation temperature, estimated to be T od ¼ 320-330 C, in order to form the ordered structure. Subsequent work by Neel et al 3 starting from single crystal fcc FeNi deduced that the L1 0 phase formed in three distinct variants, corresponding to chemical ordering along the three equivalent cubic axes of the fcc parent phase. These authors concluded that the neutron bombardment contributed to the kinetics of L1 0 formation by defect creation and atomic displacement at temperatures below Author to whom correspondence should be addressed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Irradiation was carried out below the L1 0 to fcc order-disorder transformation temperature, estimated to be T od ¼ 320-330 C, in order to form the ordered structure. Subsequent work by Neel et al 3 starting from single crystal fcc FeNi deduced that the L1 0 phase formed in three distinct variants, corresponding to chemical ordering along the three equivalent cubic axes of the fcc parent phase. These authors concluded that the neutron bombardment contributed to the kinetics of L1 0 formation by defect creation and atomic displacement at temperatures below Author to whom correspondence should be addressed.…”
mentioning
confidence: 99%
“…Its density was measured pycnometrically to be 8.15 g/cm 3 . Mo k a x-ray diffraction (XRD) and electron back-scatter diffraction (EBSD) were conducted on a polished surface of the cylinder to determine texture and crystallographic orientation, as previously reported.…”
mentioning
confidence: 99%
“…for 1 h. It is presumed that the origin of the atomic ordering induced by a short time annealing can be attributed to the heating rate dependence of ordering kinetics. These results revealed that the ordered phase is stable in the temperature range between 673 K and 813 K. It seems that the order-disorder transition temperature for the L1 0 ordered phase formed in Fe 42 Ni 41.3 Si x B 12-x P 4 Cu 0.7 (x = 4 to 8 at%) ribbons is at least higher than the reported transition temperature of 593 K. 2 Our specimen is a multicomponent system, while the previous studies had focused on binary alloys. Hence, the order-disorder transition temperature of our specimen may be affected by the constituent elements, however, the details are not clear.…”
Section: Resultsmentioning
confidence: 44%
“…8 A brief history of the investigation on tetrataenite has been reviewed in the literature. 10,12 However, the production of the ordered phase is practically difficult since the order-disorder transition temperature of this alloy was reported to be as low as 593 K. 2 Mobility of atoms is extremely low below the transition temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation